2015
DOI: 10.3851/imp3051
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Associations between Antiretroviral Therapy, Viraemia and Immunosuppression with Lipid Levels: The D:A:D Study

Abstract: Background: Antiretroviral (ART) drugs have been associated with higher triglycerides (TG), higher total cholesterol (TC) and lower high-density lipoprotein cholesterol (HDL-C) levels. Associations between lipid levels with HIV viraemia and immunosuppression in the presence of ART remain unclear. Methods: Participants from the D:A:D study with at least one TG/TC/HDL-C measurement were included. Linear mixed effect models were used to determine the association of ART, viral load (VL), nadir and current CD4 + T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…11,12 Among HIVinfected persons, associations have also been observed between markers of HIV disease progression and antiretroviral treatment responses and serum lipid concentrations. Lower CD4 T lymphocyte cell count and/or higher HIV RNA viral load (VL) have been associated with increased concentrations of triglycerides and decreased concentrations of total cholesterol, LDL-C, and HDL-C. [13][14][15][16][17][18] One epidemiologic study explored whether associations between CD4 cell count and HIV VL and markers of metabolic function, including lipid concentrations, might differ by age group, categorized in that study as <30, 30-50, and >50 years. 13 A statistically significant synergistic interaction between CD4 count and age was detected when modeling serum albumin and hemoglobin concentrations, whereby stronger positive associations between CD4 count and albumin or hemoglobin concentrations were observed among patients older than 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Among HIVinfected persons, associations have also been observed between markers of HIV disease progression and antiretroviral treatment responses and serum lipid concentrations. Lower CD4 T lymphocyte cell count and/or higher HIV RNA viral load (VL) have been associated with increased concentrations of triglycerides and decreased concentrations of total cholesterol, LDL-C, and HDL-C. [13][14][15][16][17][18] One epidemiologic study explored whether associations between CD4 cell count and HIV VL and markers of metabolic function, including lipid concentrations, might differ by age group, categorized in that study as <30, 30-50, and >50 years. 13 A statistically significant synergistic interaction between CD4 count and age was detected when modeling serum albumin and hemoglobin concentrations, whereby stronger positive associations between CD4 count and albumin or hemoglobin concentrations were observed among patients older than 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Lamivudine and telbivudine have been associated with myopathy and peripheral neuropathy, with the incidence of these effects being similar across all age groups and both genders [10]. The proposed mechanism underlying this reaction is the depletion of mitochondrial DNA [11]. An interesting report of two cases of lamivudine induced dystonia has been reported, which responded to prompt administration of anticholinergic agents and did not recur after lamivudine discontinuation [12].…”
Section: Neuropsychiatric Effects Of Antiviral Therapy For Chronic Hementioning
confidence: 99%
“…Older protease inhibitors have also been associated with an increased cardiovascular risk because of their effects on lipid metabolism (Group DADS et al, 2007). On the other hand, until recently it was thought that newer protease inhibitors (e.g., atazanavir and darunavir) did not confer these risks (Overton et al, 2012;Kamara et al, 2016;Noor et al, 2006;Yan and Hruz, 2005;Aberg et al, 2012;Monforte et al, 2013). However, recent data from the D:A:D cohort showed that darunavir was independently associated with a 59% higher risk of CVD per 5 years of exposure, while atazanavir was protective (Ryom et al, 2017).…”
Section: Use Of Safer Artmentioning
confidence: 99%